The Effect of Cooperative Learning Models with Talking Stick Method on Students’ Science Learning Competencies Class VII of SMPN 23 Padang - Reni Rahayu; Helendra Helendra; Ganda Hijrah Selaras; Ardi Ardi (ATRIUM PENDIDIKAN BIOLOGI, 2019)
ABSTRACT The low learning competency of students is caused by several problems encountered during the learning process, including the learning process centered on teacher (teacher centered). This will cause students to play an less active role, causing students learning competencies to be low. One effort was made to improve learning competencies by applying cooperative learning models with talking stick method assisted by problem question. Learning with this model requires students to play more active roles during the learning process. This study aims to reveal the effect of the use of cooperative learning models with talking stick method assisted by problem question on students learning learning competencies. This research was conducted at SMPN 23 Padang on global warming material. This research is an experimental study with the design of the Randomized Control Group Posttest Only Design. The population of this study was all students of class VII of SMPN 23 Padang. Sampling using purposive sampling technique. The research instrument used was a learning outcome test with multiple choice questions, and an attitude and skills assessment in the form of an observation sheet. Knowledge and attitude competency data use t test, while skill competency uses t’ test. The result showed that the science learning competencies of axperimental class students were higher than the control class. It can be concluded that the cooperative learning models with talking stick method assisted by questions card has a positive effect on students’ learning competencies.Keywords: (Cooperative Learning, Talking Stick Method, Learning Competencies)